A preparation method of a boron-graphite composite source for high-pressure synthesis of boron-containing nanopolycrystalline diamond

CN122897400APending Publication Date: 2026-10-13ZHENGZHOU ZHONGNAN JETE SUPERABRASIVES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320695.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0009]针对现有技术中通过物理机械混合法制备硼掺杂碳源所导致的硼元素分散不均、局部富集抑制石墨向金刚石相变、以及前驱体坯体物理性能一致性差等技术瓶颈,本发明旨在提供一种可实现硼原子级均匀分散的硼-石墨复合源的制备方法

Benefits of technology

原子级分散:利用液态前驱体在真空辅助下对多孔石墨实现分子级渗透和原位裂解,从根本上解决了硼元素的团聚问题,实现了硼在碳基体中的原子尺度均匀分散,为高压合成出硼分布均匀的纳米多晶金刚石块材奠定了基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897400A_ABST
    Figure CN122897400A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of superhard material synthesis, and particularly relates to a preparation method of a boron-graphite composite source for high-pressure synthesis of boron-containing nanometer polycrystalline diamond. The method comprises the following steps: S1: preparation of a precursor solution; S2: gradient pressure impregnation and pore filling of a porous graphite matrix; S3: solvent drying and in-situ solidification and cracking of the boron-containing precursor; and S4: high-temperature graphitization and boron-doped lattice activation. The application realizes molecular-level penetration and in-situ cracking of the porous graphite by using a liquid precursor under the assistance of vacuum, solves the agglomeration problem of boron elements, realizes atomic-scale uniform dispersion of boron in the carbon matrix, and lays a foundation for high-pressure synthesis of nanometer polycrystalline diamond bulk materials with uniform boron distribution. The boron-containing nanometer polycrystalline diamond prepared by the composite source has a grain size controllable in the range of 5-100 nm, a boron doping concentration adjustable (5-1000 ppm), a Knoop hardness greater than or equal to 100 GPa, and a fracture toughness improved by more than 30% compared with pure nanometer polycrystalline diamond.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of superhard material synthesis technology, specifically relating to a method for preparing a boron-graphite composite source for high-pressure synthesis of boron-containing nanocrystalline diamond. Background Technology

[0002] In recent years, significant progress has been made in the field of superhard materials by synthesizing nanocrystalline diamond materials via direct conversion. This method typically operates under ultra-high pressures of 14–18 GPa and ultra-high temperatures of 2300–2600 K, using non-diamond carbonaceous precursors (such as glassy carbon and highly ordered pyrolytic graphite) as raw materials. Without the use of any catalysts or binders, the structural transformation of carbon into diamond is directly achieved, yielding a completely dense bulk material composed of nanoscale grains (typically 10–100 nm in size). This material possesses a single diamond phase and a uniform microstructure, and its unique nanocrystalline structure endows it with the following excellent properties: First, its Knoop hardness can reach 120-140 GPa, exceeding the hardest crystal face of single-crystal diamond (about 115 GPa), making it the hardest material known to date. Second, since the material is composed entirely of covalently bonded nanodiamond grains and does not contain non-diamond phases at grain boundaries, it exhibits extremely high thermal stability and can withstand temperatures above 1000 ℃ in atmospheric environments without graphitization or oxidation. In addition, the material is isotropic, completely avoiding the brittle cracking problem caused by cleavage planes in single-crystal diamond, and significantly improving fracture toughness.

[0003] Based on its superior mechanical, thermal, and optical properties, large-scale nanocrystalline diamond bulk materials have been widely used in high-end cutting tools, transmission windows, and high-power heat dissipation substrates. By introducing boron doping, diamond can be further endowed with p-type semiconductor properties, thereby expanding its application potential in cutting-edge fields such as electrochemical electrodes, high-power electronic devices, and quantum sensing.

[0004] Currently, when synthesizing boron-containing nanocrystalline diamond using the high-temperature, high-pressure direct conversion method, industry and research institutions generally employ a physical-mechanical mixing process to prepare the doped carbon source to introduce boron. Specifically, micron-sized graphite powder is mixed with boron powder (or boron compound powders such as boron carbide or boron-containing solutions) through dry or wet ball milling, and then pressed into shape as a synthesis precursor. Although this process is simple and easy to implement, it has inherent physical limitations in achieving highly uniform dispersion of boron atoms, ensuring complete phase transition, and meeting the stringent requirements for precursor uniformity in large-scale synthesis.

[0005] 1. Poor uniformity of boron dispersion leads to segregation of microscopic components. Because the boron powder used typically has a particle size of 1–10 μm and high surface energy, it is prone to agglomeration, making it difficult to achieve atomic or nanoscale uniform dispersion in the graphite matrix through mechanical mixing. Research data shows (Zhang et al., *Diamond & Related Materials*, 2021) that even after 30 hours of ball milling, the size of the boron agglomerates still ranges from 0.5 to 5 μm. Furthermore, during the compaction process, the density differences among the components (graphite approximately 2.2 g / cm³, boron approximately 2.3 g / cm³, B4C approximately 2.5 g / cm³) further exacerbate the compositional gradient, leading to a severely uneven distribution of boron concentration in the synthesized diamond. Experimental measurements (Chen et al., *Journal of Applied Physics*, 2019) show that the boron content in local areas can fluctuate by ±40%. This microscopic inhomogeneity triggers a "bottleneck effect" in electrical and mechanical properties, significantly reducing the consistency of device performance.

[0006] 2. Local boron enrichment inhibits the phase transition from carbon to diamond. Excessive local boron concentration can "poison" the graphite-diamond transformation process, hindering the phase transition. For example, in preliminary experiments of this invention, it was found that when synthesizing diamond blocks with a diameter of 15 mm using a B4C / graphite mixed source prepared by conventional ball milling, the diamond conversion rate decreased by about 30% in the agglomerated region due to uneven boron dispersion, accompanied by a large amount of unconverted carbon. The Knoop hardness in this region decreased by 15% to 20% compared to the uniform region, and the infrared transmittance (10 μm wavelength) was less than 50%.

[0007] 3. Inconsistent physical properties of the billet affect the stability and repeatability of high-pressure synthesis. The preforms prepared by the physical mixing method exhibit significant batch-to-batch variations in density, porosity, and mechanical strength. Actual measurements show that density fluctuations between different batches can reach ±0.3 g / cm³. In high-pressure chambers, these preforms, due to inconsistent deformation behavior, disrupt the uniform distribution of pressure and temperature fields, especially during large-size synthesis (e.g., diameter > 15 mm), easily leading to stress concentration and crack initiation, resulting in low product yield. Industry statistics show that the yield of large-scale boron-containing nanocrystalline diamond synthesized using traditional mixed-source methods is generally below 60%, becoming a major factor restricting its industrial application.

[0008] In summary, existing physical mixing methods for preparing doped carbon sources have significant shortcomings in terms of uniformity, phase transition behavior, and process adaptability, which has become a technical bottleneck for achieving large-scale preparation of high-performance, large-size boron-containing nanocrystalline diamond. Summary of the Invention

[0009] To address the technical bottlenecks in existing boron-doped carbon source preparation methods, such as uneven boron dispersion, localized enrichment inhibiting the graphite-diamond phase transition, and poor consistency of physical properties in precursor preforms, this invention aims to provide a method for preparing a boron-graphite composite source that achieves atomic-level uniform boron dispersion. This composite source is specifically designed for high-temperature, high-pressure direct conversion to stably synthesize large-scale, high-performance boron-containing nanocrystalline diamond bulk materials, ensuring the uniformity and reliability of their electrical and mechanical properties.

[0010] This invention provides a method for preparing a boron-graphite composite source for high-pressure synthesis of boron-containing nanocrystalline diamond, comprising the following steps: S1: Preparation of precursor solution The selected boron-containing organic precursor was dissolved in a low-boiling-point organic solvent and stirred thoroughly until completely dissolved to obtain a homogeneous impregnation solution with a concentration of 0.01–5.0 mol / L.

[0011] The boron-containing organic precursor is selected from trimethyl borate, triethyl borate, phenylboronic acid, or any combination thereof; the organic solvent is selected from methanol, ethanol, acetone, tetrahydrofuran, or mixed solvents thereof. The concentration range is set with dual considerations: the lower limit of 0.01 mol / L ensures the solution has low viscosity and high fluidity to guarantee complete penetration and wetting of the porous graphite micropores; the upper limit of 5.0 mol / L balances the complete solubility of the solute with the storage stability of the solution, and works in conjunction with the subsequent impregnation-pyrolysis cycle process to achieve precise control of the boron content in the final composite source within a wide range of 5–1000 ppm.

[0012] S2: Gradient pressure impregnation and pore filling of porous graphite matrix (I) High-temperature purification pretreatment The formed porous graphite preform is placed in a high-temperature furnace under vacuum or inert atmosphere protection. The porous graphite preform has a porosity of 15% to 45% and a purity of ≥99.9 wt%. The temperature is raised to 1800 to 2400°C at a rate of 5 to 10°C / min and held for 1 to 3 hours.

[0013] The pretreatment has three functions: (1) Based on the significant difference in vapor pressure of different impurity elements (such as metal oxides and sulfides), the high temperature field is used to promote their selective volatilization and removal, thereby increasing the purity of graphite to over 99.99%; (2) Eliminate the macroscopic internal stress left by the graphite blank during mechanical forming, and stabilize its dimensional accuracy and microstructure integrity; (3) Induce thermal rearrangement of graphite microcrystals, causing some of the originally closed pores to be transformed into interconnected open pores. At the same time, the high temperature cleans the adsorbed impurities on the inner wall surface of the pores, significantly improving the surface energy of the graphite matrix and providing good interfacial wetting conditions for the subsequent impregnation solution.

[0014] (ii) Vacuum degassing The high-purity porous graphite preform, after being purified at high temperature, is placed into a vacuum impregnation device equipped with a sealed chamber, a vacuum system, and a liquid injection unit; the vacuum system is activated to evacuate the sealed chamber until the absolute pressure inside is lower than 10 Pa, and this vacuum level is maintained for no less than 30 minutes.

[0015] The purpose of this stage of the process is to use a continuous negative pressure environment to force the desorption and discharge of gas molecules and residual low-boiling-point volatiles adsorbed inside the pores of the graphite blank, thereby avoiding the "gas blockage" effect caused by bubbles trapped in the pores during subsequent liquid phase immersion, and creating a smooth channel for the unobstructed transport of the solution in the capillary network.

[0016] (III) Negative pressure absorption and initial wetting While maintaining a vacuum of <10 Pa in the sealed chamber, the impregnation solution prepared in step S1 is introduced into the chamber at a constant and controllable flow rate through the liquid injection unit until the liquid surface completely submerges the graphite blank, and this vacuum state is maintained for 0.5 to 2 hours.

[0017] During this stage, the solution is dynamically drawn into the open pores of the surface and subsurface of the green body by the capillary force of the inner wall of the pores and the micro-negative pressure suction effect of the residual low pressure zone deep in the pores, thus completing the initial wetting and preliminary penetration of the solid-liquid interface.

[0018] (iv) Positive pressure differential forced osmosis Keep the solution completely submerged in the blank, and introduce high-purity inert gas (such as argon) or dried and filtered clean gas into the sealed chamber at a slow rate of 0.5 to 2 kPa / s to allow the system pressure to steadily return to atmospheric pressure (approximately 101 kPa).

[0019] During this pressurization process, the external environmental pressure of the chamber gradually increases, while the deep micropores inside the billet maintain a relatively low residual pressure due to the lag effect of the liquid front advancement. This creates a transient positive pressure gradient (ΔP≈0.1 MPa) from the surface to the interior along the cross-sectional direction of the billet. This pressure gradient serves as the core driving force, propelling the impregnation solution within the chamber to overcome capillary resistance and continuously penetrate into the middle and deep open pores of the billet, ensuring uniform, continuous, and sufficient filling of the solution across the entire thickness of the graphite billet.

[0020] (v) Static diffusion and adsorption equilibrium After restoring normal pressure, keep the green body completely immersed in the solution and let it stand for at least 2 hours.

[0021] This stage aims to achieve a macroscopically uniform distribution of the solution system enriched within the pores through molecular diffusion, and to promote the full physical adsorption of boron-containing organic precursor molecules on the surface of graphite microcrystals and the inner walls of the pores through van der Waals forces and π-π interactions, thereby achieving adsorption equilibrium at the solid-liquid interface and laying the foundation for a uniform precursor distribution for subsequent in-situ transformation.

[0022] S3: Solvent drying and in-situ solidification and pyrolysis of boron-containing precursors (a) Gradient temperature controlled drying The graphite billet saturated by impregnation in step S2 is transferred to an inert atmosphere treatment device equipped with a precision temperature control system and an atmosphere control unit (this device is selected from a tube furnace, an atmosphere box furnace, or a combination thereof, and is equipped with an inert gas supply and flow control unit). Under a protective atmosphere of continuously flowing high-purity inert gas (such as argon or nitrogen, flow rate 0.5–2 L / min), it is heated to 50–120°C at a low heating rate of 0.5–2°C / min. The drying endpoint is determined by the change rate of the billet mass not exceeding 0.1% for 30 consecutive minutes.

[0023] Within this temperature range, multiple insulation platforms can be set up for segmented gradient drying.

[0024] During the drying process, the impregnation solution within the pores gradually concentrates due to continuous solvent evaporation. Driven by the concentration gradient, the dissolved boron-containing organic precursor is oriented towards the inner surface of the pores and adheres firmly. As the solvent phase is completely removed, precursor molecules precipitate in situ on the surface of the graphite microcrystals and the inner walls of the pores, forming a thin, uniformly thick solid film. This effectively avoids the drawback of solute migration with the solvent to the pore openings, leading to pore blockage. The drying endpoint is determined by a change in the mass of the green body not exceeding 0.1% for 30 consecutive minutes, indicating that the organic solvent has been completely removed.

[0025] (II) Temperature-controlled pyrolysis and chemical anchoring After the drying process is completed, under the condition of maintaining a continuous flow of inert atmosphere, the temperature is programmed to rise to the preset pyrolysis temperature of 600-1000℃ at a constant heating rate of 1-5℃ / min, and held at this temperature for 0.5-3 hours.

[0026] During this heating and holding process, the boron-containing organic precursor loaded on the inner wall of the graphite pores undergoes in-situ thermal decomposition: its organic ligands (such as alkyl and aromatic groups) break bonds and escape in the form of gaseous hydrocarbons or small molecule hydrocarbons; the boron element detaches from the organic framework and transforms into highly active amorphous boron species or BC nanoclusters, which are then firmly anchored to the carbon framework of the graphite matrix through the following dual mechanisms: (1) Chemical bonding mechanism: Active boron atoms react with suspended carbon atoms at the edge of the graphite surface and lattice defect sites to form stable BC covalent bonds; (2) Physical confinement mechanism: Some boron species are embedded in the interlayer of graphite microcrystals or pinned to the edge dislocations, achieving irreversible fixation through a combination of physical confinement and chemical adsorption.

[0027] Through this pyrolysis step, the boron-containing precursor is irreversibly transformed from a soluble molecular state into a solid active boron-containing species (existing in the form of amorphous boron or boron-carbon nanocomposites), achieving atomic-level dispersion and loading "from the surface to the interior, layer by layer uniformly" along the surface of the graphite preform to the inner wall of the deep pores.

[0028] Based on the target boron doping amount requirement, the mass fraction of boron in the final boron-graphite composite source can be precisely controlled within the range of 5 ppm to 1000 ppm by adjusting the concentration of the impregnation solution in step S1 (0.01–5.0 mol / L) and / or repeating the process cycles of steps S2 to S3 (1–5 times).

[0029] In each cycle, the newly introduced impregnation solution can continue to penetrate and fill the newly exposed or residual pore spaces after the previous pyrolysis, realizing the layer-by-layer superposition and uniform incremental doping of boron-containing species in the three-dimensional pore network.

[0030] S4: High-temperature graphitization and boron-doped lattice activation.

[0031] The carbon composite preform after the low-temperature pyrolysis treatment in step S3 (whose carbon matrix is ​​mainly pyrolytic carbon or disordered layered carbon, with carbon atom layers stacked in a disordered or short-range ordered manner, and not yet forming a three-dimensional long-range ordered graphite lattice; at the same time, the loaded boron species at this time mostly exist in amorphous clusters or interface enrichment states) is placed in a high-temperature graphitization furnace, and heated to 2000-2500 ℃ at a rate of 5-10 ℃ / min under the protection of inert gas (such as argon) or vacuum environment, and held for 1-4 hours to carry out high-temperature graphitization and doping activation integrated treatment.

[0032] The core technological logic and necessity of this step are as follows: (1) Graphite lattice reconstruction: The carbon skeleton of the preform obtained in step S3 is still in a thermodynamic metastable state. Sufficient activation energy provided by a high temperature above 2000℃ is required to induce long-range diffusion and rearrangement of the disordered layered carbon atoms, completing the complete transformation from a disordered layered structure to a three-dimensional ordered hexagonal graphite lattice (AB stacking). After this treatment, the electrical conductivity, thermal conductivity and high-temperature thermal stability of the composite source are significantly improved to meet the heat transfer and electrical conductivity physical field requirements for the synthesis of diamond under ultra-high pressure and high temperature (HPHT).

[0033] (2) Lattice doping activation of boron species: This high-temperature stage is not only the graphitization process of the carbon matrix, but also a key activation step for the migration of boron elements from interstitial sites or surface clusters into the interior of the graphite lattice. Driven by high temperature, amorphous boron atoms loaded on the surface gain sufficient kinetic energy to occupy carbon atom sites in the graphite lattice by substitution or to insert into the graphite interlayer to form intercalation structures, thereby constructing a substitutional / intercalation type boron-doped graphite lattice with atomic-level dispersion characteristics and stable structure. At the same time, high-temperature treatment can eliminate amorphous carbon residues introduced by precursor pyrolysis, promoting a highly ordered graphite matrix structure. This activated boron source is an indispensable material basis for the subsequent high-pressure synthesis of boron-containing nanocrystalline diamond.

[0034] (3) The irreplaceability of the low-temperature pyrolysis pre-step: It is strictly forbidden to combine steps S3 and S4 into a process of "directly heating to the graphitization high temperature in one step". The fundamental limiting factor is that in the low temperature range (300~1000 ℃), the pyrolysis reaction of organic precursors is violent, accompanied by the continuous precipitation of a large number of gaseous small molecule products such as CO2, CH4, and H2. If the temperature is directly crossed to 2000℃ or above, on the one hand, the internal accumulated gas will be released instantly due to the rapid expansion at high temperature, causing the bulk volume to expand, macroscopic cracking or even explosion, resulting in the overall scrapping of the product; on the other hand, the surface carbon skeleton will be sintered and densified first at high temperature, forming a rigid hard shell layer. This hard shell layer will seriously block the outward diffusion channel of volatiles inside the bulk, resulting in a loose core, severely uneven density distribution or interlayer peeling defects, fundamentally deteriorating the mechanical strength and structural uniformity of the composite source. Therefore, it is essential to strictly implement a step-by-step heat treatment process of "first low-temperature full pyrolysis and degassing, then high-temperature graphitization and activation" to ensure the integrity and performance uniformity of the products.

[0035] The boron-graphite composite source prepared by steps S1 to S4 has a bulk density of 1.70 to 1.85 g / cm³, a compressive strength of ≥80 MPa, and macroscopic physical properties that are highly consistent with those of undoped high-purity graphite source. Boron is uniformly dispersed at the atomic scale in the lattice defects, interlayers, or surface of the graphite matrix.

[0036] This invention also provides a method for synthesizing boron-containing nanocrystalline diamond using the above-mentioned boron-graphite composite source, the method comprising the following steps: Step 1: Construction of high-pressure synthesis assembly The boron-graphite composite source obtained in step S4 is processed into a pre-defined cylindrical or sheet-like blank and placed into a high-pressure synthesis assembly. The assembly, from the inside out, includes: the composite source blank, a heating element (such as a graphite tube or Ta tube), a pressure-transmitting medium layer (such as pyrophyllite, dolomite, or hexagonal boron nitride), a conductive ring, and a sealing component. During assembly, it is ensured that the composite source blank, heating element, and conductive ring form a complete current loop to guarantee a uniform temperature distribution within the high-pressure cavity.

[0037] Step 2: Installation and pressurization of the ultra-high pressure and high temperature device The assembled block from step 1 is placed at the center of the working cylinder of a six-sided or two-sided press. The hydraulic system is activated, and the chamber pressure is increased to a composite pressure of 10–20 GPa (preferably 10–15 GPa) at a pressurization rate of 5–20 MPa / min. During the pressurization process, the top hammers are fed synchronously to ensure that the pressure field is in a quasi-isostatic state, thus avoiding deformation or breakage of the billet due to bias pressure.

[0038] Step 3: Heating and Pressure Holding After the synthesis pressure reaches the target value and stabilizes, the heating power supply is activated, and the chamber temperature is raised to a synthesis temperature of 1200–2000 °C (preferably 1400–1800 °C) at a rate of 50–200 °C / min. After reaching the target temperature, the chamber is held at this temperature and pressure for 10–120 minutes (preferably 20–60 minutes). Under this ultra-high pressure and high temperature condition, the graphite layer in the boron-graphite composite source undergoes a martensitic or diffusion-type phase transformation to a diamond structure. Boron atoms enter the diamond lattice through substitution, and the polycrystalline grains undergo dynamic recrystallization and densification under high pressure, forming a polycrystalline sintered body with nanoscale diamond grains (grain size ≤100 nm) as the main phase and a small amount of amorphous carbon or B4C transition phase at the grain boundaries.

[0039] Step 4: Cooling and depressurization After the heat preservation and pressure holding stage, the cavity temperature is reduced to below room temperature at a rate of 100–300 °C / min (circulating water cooling can be used to lower the temperature of the surrounding components); once the temperature drops below 300 °C, the cavity pressure is slowly released to atmospheric pressure at a rate of 5–15 MPa / min. The cooling and depressurization processes must be coordinated and controlled to avoid thermal-mechanical coupling impact that could cause the synthesized bulk material to crack or microcracks to form in the diamond sintered body.

[0040] Step 5: Post-processing and product recovery The synthesized block is removed from the press, and the peripheral pressure transmission medium, heating element, and sealing components are removed sequentially to peel off the boron-containing nanocrystalline diamond sintered body. The obtained sintered body is boiled in aqua regia or a mixture of concentrated sulfuric acid and concentrated nitric acid for 30-60 minutes to remove residual metal catalysts or impurities on the surface; then it is ultrasonically cleaned with deionized water until the washing solution is neutral, and dried in an oven at 80-120 °C to constant weight to obtain the boron-containing nanocrystalline diamond finished product.

[0041] The boron-containing nanocrystalline diamond prepared by this invention has the following characteristics: the grain size is controllable in the range of 5–100 nm, the boron doping concentration is adjustable (5–1000 ppm), the Knoop hardness is ≥100 GPa, the fracture toughness is improved by more than 30% compared with pure nanocrystalline diamond, and the thermal stability reaches over 1000 ℃. This material is suitable for precision machining tools, cutting of high-hardness materials, anvils for high-pressure physics experiments, and heat dissipation substrates for semiconductor devices.

[0042] The beneficial effects of this invention are: Atomic-level dispersion: By using liquid precursors under vacuum assistance to achieve molecular-level penetration and in-situ pyrolysis of porous graphite, the problem of boron agglomeration is fundamentally solved, and the uniform atomic-scale dispersion of boron in the carbon matrix is ​​achieved, laying the foundation for high-pressure synthesis of uniformly distributed boron nanocrystalline diamond bulk materials.

[0043] Promoting high-pressure phase transformation: Uniformly dispersed boron species can act as "seeds" or "catalyst modifiers" under high pressure and high temperature, effectively reducing the poisoning effect of local high boron concentration on graphite→diamond phase transformation, which is beneficial to improving conversion rate and product purity.

[0044] Excellent process compatibility: Through high-temperature graphitization treatment, the composite source is ensured to have density, strength and thermal stability similar to that of pure graphite source, which guarantees the uniformity of stress and heat transfer in the high-pressure cavity, making it particularly suitable for the stable synthesis of large-size nano-polycrystalline diamond bulk materials.

[0045] Precise and controllable doping concentration: By adjusting the precursor solution concentration and the number of impregnations (1-5 times), the boron doping concentration can be linearly and precisely controlled, with good process repeatability, which facilitates customized production for products with different electrical performance requirements. Attached Figure Description

[0046] Figure 1 This is a photograph of the boron-graphite composite source prepared in Example 1.

[0047] Figure 2Comparison of the boron element electron probe microanalysis (EPMA) surface distribution of the cross-section of the boron-containing nanocrystalline diamond bulk material obtained after high-pressure synthesis of the synthetic sources prepared in Comparative Example 1 (physical mixing method) and Example 1 (method of the present invention) (left: Comparative Example 1; right: Example 1).

[0048] Figure 3 The image shows a cross-sectional scanning electron microscope (SEM) image of the boron-containing nanocrystalline diamond bulk material obtained by high-pressure synthesis of the synthetic source prepared in Comparative Example 1 (physical mixing method).

[0049] Figure 4 The image shows a cross-sectional scanning electron microscope (SEM) image of boron-containing nanocrystalline diamond bulk material obtained by high-pressure synthesis of the synthetic source prepared in Example 1 (the method of the present invention).

[0050] Figure 5 The image shows a cross-sectional scanning electron microscope (SEM) image of the boron-containing nanocrystalline diamond bulk material obtained by high-pressure synthesis of the synthetic source prepared in Example 2 (the method of the present invention).

[0051] Figure 6 The image shows a cross-sectional scanning electron microscope (SEM) image of the boron-containing nanocrystalline diamond bulk material obtained by high-pressure synthesis of the synthetic source prepared in Example 3 (the method of the present invention).

[0052] Figure 7 The Knoop hardness of the boron-containing nanocrystalline diamond block obtained by high-pressure synthesis of the synthetic source prepared in Example 1 (the method of the present invention) is shown.

[0053] Figure 8 The X-ray diffraction pattern of the boron-containing nanocrystalline diamond bulk material obtained after high-pressure synthesis using the synthetic source prepared in Example 1 (the method of the present invention) showed no B4C / B3C2 diffraction peaks and no graphite (002) diffraction peaks. Detailed Implementation

[0054] The present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited thereto. Example

[0055] 1. Preparation of boron-graphite composite source S1: Preparation of precursor solution Triethyl borate was dissolved in anhydrous ethanol and stirred thoroughly until completely dissolved to obtain a homogeneous impregnation solution with a concentration of 0.5 mol / L.

[0056] S2: Gradient pressure impregnation and pore filling of porous graphite matrix. Select a porous graphite preform with a porosity of 25% and a purity ≥ 99.9 wt%, and process it according to the following procedure: (1) High temperature purification pretreatment: The porous graphite blank is placed in a vacuum high temperature furnace and heated to 2000 ℃ at a rate of 8 ℃ / min. It is kept at the temperature for 2 hours to increase the graphite purity to more than 99.99%.

[0057] (2) Vacuum degassing: Place the purified blank into a vacuum impregnation device, evacuate to an absolute pressure of less than 10 Pa, and maintain for 30 minutes.

[0058] (3) Negative pressure absorption and initial wetting: Keep the vacuum level constant, introduce the impregnation solution prepared in step S1 into the chamber until the liquid surface completely submerges the blank, and continue to maintain the vacuum state for 1 hour.

[0059] (4) Positive pressure difference forced permeation: High-purity argon gas is introduced into the chamber at a rate of 1 kPa / s to restore the system pressure to normal pressure (about 101 kPa). The internal and external pressure difference (ΔP≈0.1 MPa) is used to drive the solution to force permeation into the deep pores of the billet.

[0060] (5) Static diffusion and adsorption equilibrium: After restoring normal pressure, keep the green body completely immersed in the solution and let it stand for 2 hours.

[0061] S3: Solvent drying and in-situ solidification and pyrolysis of boron-containing precursors (1) Gradient temperature control drying: Transfer the impregnated saturated billet to a tube furnace and dry it in sections at 1℃ / min with argon protection (flow rate 1 L / min) until the change rate of billet mass does not exceed 0.1% for 30 consecutive minutes.

[0062] (2) Temperature-controlled thermal pyrolysis and chemical anchoring: After drying, the temperature is increased to 800℃ at 3℃ / min and held for 1.5 hours for thermal pyrolysis, so that the boron-containing precursor is converted into active boron species and anchored to the graphite skeleton by BC covalent bonds.

[0063] This embodiment only performs one "immersion-drying-pyrolysis" cycle.

[0064] S4: High-temperature graphitization and boron-doped lattice activation The pyrolyzed billet was placed in a high-temperature graphitization furnace and heated to 2200 ℃ at a rate of 8 ℃ / min under argon protection, and held at that temperature for 2 hours to obtain a boron-graphite composite source. Figure 1 (A photograph of the composite source obtained in this embodiment).

[0065] The composite source obtained through the above steps has a boron mass fraction of approximately 180 ppm, a bulk density of 1.78 g / cm³, and a compressive strength of 95 MPa.

[0066] 2. High-pressure synthesis of boron-containing polycrystalline diamond nanoparticles (1) Construction of high-pressure synthesis assembly The aforementioned boron-graphite composite source was processed into a cylindrical blank (10 mm in diameter and 8 mm in height) and placed into a high-pressure synthesis assembly. The assembly, from the inside out, comprises: the composite source blank, a high-purity graphite heating element (1 mm wall thickness), a pyrophyllite pressure-transmitting medium layer (3–5 mm thickness), a molybdenum conductive ring, and a pyrophyllite sealing component. During assembly, it was ensured that the composite source blank, heating element, and conductive component formed a complete current loop.

[0067] (2) Ultra-high pressure and high temperature synthesis The assembled composite block is placed in the center of the working cylinder of a domestically produced hinged six-sided top press.

[0068] - Pressurization stage: Start the hydraulic system to increase the chamber pressure to 15 GPa at a pressurization rate of 10 MPa / min.

[0069] - Heating and Pressure Holding Stage: After the synthesis pressure reaches and stabilizes at 15 GPa, the heating power supply is activated, and heating is carried out at a rate of 100℃ / min to raise the chamber temperature to 2000℃. After reaching the target temperature, constant power supply is maintained for 30 minutes of pressure holding. Under these ultra-high pressure and high temperature conditions, the graphite layer in the boron-graphite composite source undergoes a direct phase transition to a diamond structure, with boron atoms entering the diamond lattice through substitution.

[0070] - Cooling and depressurization stage: After the heat preservation and pressure preservation are completed, the heating power supply is cut off at a rate of 200℃ / min to allow the cavity temperature to drop to room temperature; after the temperature drops below 300℃, the cavity pressure is slowly depressurized to normal pressure at a rate of 10 MPa / min.

[0071] (3) Post-processing and product recovery The synthesized block was removed from the press, and the peripheral pressure transmission medium, heating element, and sealing components were removed in sequence to peel off the boron-containing nanocrystalline diamond sintered body. The obtained sintered body was boiled in aqua regia for 45 minutes to remove residual impurities on the surface; then it was ultrasonically cleaned with deionized water until the washing solution was neutral, and dried in an oven at 100 °C to constant weight to obtain the boron-containing nanocrystalline diamond finished product.

[0072] Product characterization The obtained boron-containing nanocrystalline diamond bulk material was a brownish-yellow transparent bulk with a uniform color. Scanning electron microscopy (SEM) observations (see Figure 4) showed that the sample cross-section had a dense structure with no obvious pores, inclusions, or microscopic defects. Electron probe microanalysis (EPMA) surface scanning results (see Figure 2, right side) confirmed that boron was atomically uniformly distributed across the cross-section of the bulk material, with no regions of boron enrichment or depletion. Synchrotron radiation X-ray diffraction (see Figure 8) did not detect characteristic diffraction peaks of graphite phase and boron-carbon compounds, proving that the graphite precursor had completely transformed into the diamond phase. The sample's Knoop hardness (see Figure 7) was ≥100 GPa, and its fracture toughness was 30% higher than that of undoped pure nanocrystalline diamond. Example

[0073] Preparation of boron-graphite composite source The difference from Example 1 is as follows: - S1: Dissolve phenylboronic acid in tetrahydrofuran to obtain an impregnation solution with a concentration of 2.0 mol / L; - S2 to S3: Repeat the "impregnation-drying-pyrolysis" cycle 3 times to achieve a higher boron loading; - S4: Graphitization temperature increased to 2400℃, held for 3 hours.

[0074] The composite source obtained through the above steps has a boron mass fraction of approximately 850 ppm, a bulk density of 1.82 g / cm³, and a compressive strength of 88 MPa.

[0075] 2. High-pressure synthesis of boron-containing polycrystalline diamond nanoparticles The synthesis parameters were as follows: synthesis pressure 15 GPa, synthesis temperature 2000℃, and holding time 60 minutes. The post-processing steps were the same as in Example 1.

[0076] 3. Product Characterization The obtained boron-containing nanocrystalline diamond bulk material was a dark brown, semi-transparent to transparent bulk. Compared to the sample in Example 1, the yellow hue was deeper, almost black, with only a slight yellowish tint. Scanning electron microscopy (SEM) observations (see Figure 5) showed that the sample had uniform grain size, dense structure, and no obvious porosity or microscopic defects. EPMA surface distribution analysis confirmed that boron was uniformly distributed across the sample cross-section, without any boron enrichment or depletion. The sample had a Knoop hardness ≥100 GPa, and its fracture toughness was more than 25% higher than that of undoped pure nanocrystalline diamond. Example

[0077] 1. Preparation of boron-graphite composite source The difference from Example 1 is as follows: in S1, trimethyl borate was dissolved in methanol to obtain an impregnation solution with a concentration of 0.05 mol / L; in S2 and S3, only one "impregnation-drying-pyrolysis" cycle was performed; in S4, the graphitization temperature was 2000℃, and the temperature was maintained for 1 hour. The composite source prepared by the above steps has a boron mass fraction of approximately 15 ppm, a bulk density of 1.75 g / cm³, and a compressive strength of 98 MPa.

[0078] 2. High-pressure synthesis of boron-containing polycrystalline diamond nanoparticles The synthesis parameters are as follows: synthesis pressure 12 GPa, synthesis temperature 1800℃, and holding time 20 minutes. The post-processing steps are the same as in Example 1.

[0079] Product characterization The obtained boron-containing nanocrystalline diamond bulk has a dense and uniform overall structure, with no obvious impurity phases, pores, or macroscopic defects observed. The sample is yellowish-brown, the lightest in color among the three sets of sample examples. EPMA analysis shows that boron is uniformly dissolved within the diamond lattice at the atomic scale, without local enrichment or depletion. The sample exhibits atmospheric thermal stability exceeding 1000℃; its Knoop hardness is not less than 100 GPa, and its fracture toughness is 10% or more higher than that of undoped pure nanocrystalline diamond.

[0080] Comparative Example 1 (Physical Mixing Method) In contrast, a boron-graphite synthesis source was prepared using a physical mixing method: high-purity graphite powder with a purity ≥99.9wt% and nano-boron powder were ball-milled to the target boron content (180 ppm) (argon protection, ball-to-powder ratio 10:1, rotation speed 300 rpm, mixing time 4 hours), and then the mixed powder was pressed into a compact and sintered. The remaining high-pressure synthesis conditions were exactly the same as in Example 1.

[0081] Figure 2 The EPMA boron surface distribution of the products obtained in Comparative Example 1 and Example 1 is shown as a comparison. Figure 3 and Figure 4 SEM cross-sectional images of the products obtained in Comparative Example 1 and Example 1 are shown respectively. Figure 2 It is evident that the boron distribution in the bulk material obtained in Comparative Example 1 is extremely uneven, with distinct boron-rich and boron-poor regions; while the boron in the bulk material obtained in Example 1 exhibits atomic-level uniform dispersion. Figure 3 Figure 4As can be seen, the boron element in the bulk material obtained in Comparative Example 1 is agglomerated, with obvious porosity and defects; while the bulk material obtained in Example 1 has a uniform color and a dense structure. The above comparison fully demonstrates that the method of the present invention, through the technical path of liquid phase impregnation-in-situ pyrolysis-high temperature graphitization, achieves atomic-level uniform dispersion of boron element in the graphite matrix, thereby ensuring the uniformity of boron doping and the integrity of the structure in the high-pressure synthesis product.

[0082] Basis for selecting process parameters The selection of parameters such as synthesis pressure and temperature in the above embodiments is based on the following criteria: 1. Pressure Range (12–15 GPa): The direct phase transformation from graphite to diamond requires extremely high hydrostatic pressure. Studies have shown that graphite can be directly converted into nano-polycrystalline diamond under conditions of ≥15 GPa and 2000℃. Domestically produced six-sided top presses can achieve ultra-high pressure and high temperature synthesis conditions of 12–15 GPa and 1800–2000℃.

[0083] 2. Temperature range (1800~2000℃): The temperature needs to be high enough to overcome the activation energy of the graphite→diamond phase transition, while avoiding excessively high temperatures that could cause diamond to undergo reverse phase transition graphitization. In boron-containing systems, the introduction of boron can reduce the phase transition temperature to some extent.

[0084] 3. Holding time (20-60 minutes): It is necessary to ensure the complete transformation of graphite into diamond and the full recrystallization and densification of the grains, while avoiding excessive grain growth.

[0085] The above experimental results fully demonstrate that the boron-graphite composite source and its preparation method provided by this invention are significantly superior to the traditional physical mixing method in terms of achieving boron atomic-level dispersion, ensuring high-pressure synthesis stability, and improving the overall performance of the final boron-containing nanocrystalline diamond bulk material.

[0086] This invention promotes the application of boron-containing nanocrystalline diamond in high-end fields such as semiconductor devices, optical windows, and thermal management components by improving the dispersion, phase transition compatibility, and synthesis process stability of boron in carbon sources.

[0087] This invention is not limited to the specific embodiments described above. Any modifications, equivalent substitutions, or improvements made by those skilled in the art without departing from the principles and spirit of this invention should be included within the scope of protection of this invention.

Claims

1. A method for preparing a boron-graphite composite source for high-pressure synthesis of boron-containing nanocrystalline diamond, comprising the following steps: S1: Preparation of precursor solution The selected boron-containing organic precursor was dissolved in a low-boiling-point organic solvent and stirred thoroughly until completely dissolved to obtain a homogeneous impregnation solution with a concentration of 0.01–5.0 mol / L. S2: Gradient pressure impregnation and pore filling of porous graphite matrix (I) High-temperature purification pretreatment The formed porous graphite preform is placed in a high-temperature furnace under vacuum or inert atmosphere protection. The porous graphite preform has a porosity of 15% to 45% and a purity of ≥99.9 wt%. The temperature is raised to 1800 to 2400 ℃ at a rate of 5 to 10 ℃ / min and held for 1 to 3 hours. (ii) Vacuum degassing The high-purity porous graphite preform, after being purified at high temperature, is placed into a vacuum impregnation device equipped with a sealed chamber, a vacuum system, and a liquid injection unit; the vacuum system is activated to evacuate the sealed chamber until the absolute pressure inside is lower than 10 Pa, and this vacuum level is maintained for no less than 30 minutes. (III) Negative pressure absorption and initial wetting While maintaining a vacuum of <10 Pa in the sealed chamber, the impregnation solution prepared in step S1 is introduced into the chamber at a constant and controllable flow rate through the liquid injection unit until the liquid surface completely submerges the graphite blank, and this vacuum state is maintained for 0.5 to 2 hours. (iv) Positive pressure differential forced osmosis Keep the solution completely submerged in the blank, and introduce high-purity inert gas or dried and filtered clean gas into the sealed chamber at a slow rate of 0.5 to 2 kPa / s to allow the system pressure to return to normal pressure. (v) Static diffusion and adsorption equilibrium After restoring normal pressure, keep the green body completely immersed in the solution and let it stand and soak for no less than 2 hours; S3: Solvent drying and in-situ solidification and pyrolysis of boron-containing precursors (a) Gradient temperature controlled drying The graphite blank saturated by impregnation in step S2 is transferred to an inert atmosphere treatment device equipped with a precision temperature control system and an atmosphere control unit. Under the protective atmosphere of continuous introduction of high-purity inert gas, it is heated to 50-120 ℃ at a low heating rate of 0.5-2 ℃ / min. The drying endpoint is determined by the change rate of the blank mass not exceeding 0.1% within 30 consecutive minutes. (II) Temperature-controlled pyrolysis and chemical anchoring After the drying process is completed, under the condition of maintaining a continuous flow of inert atmosphere, the temperature is programmed to rise to the preset pyrolysis temperature of 600-1000 ℃ at a constant heating rate of 1-5 ℃ / min, and held at this temperature for 0.5-3 hours. Based on the target boron doping amount requirement, the mass fraction of boron in the final boron-graphite composite source can be precisely controlled within the range of 5 ppm to 1000 ppm by adjusting the concentration of the impregnation solution in step S1 and / or repeating the process cycles of steps S2 to S3 (1-5 cycles). S4: High-temperature graphitization and boron-doped lattice activation; The carbonaceous composite preform after the low-temperature pyrolysis treatment in step S3 is placed in a high-temperature graphitization furnace. Under inert gas protection or vacuum environment, the temperature is raised to 2000-2500 ℃ at a rate of 5-10 ℃ / min and held for 1-4 hours to carry out integrated high-temperature graphitization and doping activation treatment.

2. The preparation method according to claim 1, characterized in that, In step S1, the boron-containing organic precursor is selected from trimethyl borate, triethyl borate, phenylboronic acid, or any combination thereof; the organic solvent is selected from methanol, ethanol, acetone, tetrahydrofuran, or mixed solvents thereof.

3. The boron-graphite composite source prepared by the preparation method according to claim 1 or 2.

4. The boron-graphite composite source according to claim 3, characterized in that, The bulk density is 1.70–1.85 g / cm³, the compressive strength is ≥80 MPa, and the boron element is uniformly dispersed at the atomic scale in the lattice defects, interlayers or surface of the graphite matrix.

5. The method for synthesizing boron-containing nanocrystalline diamond using the boron-graphite composite source according to claim 3, characterized in that, Includes the following steps: Step 1: Construction of high-pressure synthesis assembly The obtained boron-graphite composite source is processed into a pre-designed cylindrical or sheet-like blank and placed into a high-pressure synthesis assembly. Step 2: Installation and pressurization of the ultra-high pressure and high temperature device Place the assembled composite block from step 1 at the center of the working cylinder of a six-sided or two-sided press, start the hydraulic system, and increase the chamber pressure to a composite pressure of 10-20 GPa at a pressurization rate of 5-20 MPa / min. Step 3: Heating and Pressure Holding After the synthesis pressure reaches the target value and stabilizes, the heating power supply is turned on to raise the temperature of the chamber to the synthesis temperature of 1200-2000 ℃ at a rate of 50-200 ℃ / min; after reaching the target temperature, the chamber is kept at this temperature and pressure for 10-120 minutes. Step 4: Cooling and depressurization After the heat preservation and pressure holding stage is completed, the temperature of the cavity is reduced to below room temperature at a rate of 100-300 ℃ / min; after the temperature drops below 300 ℃, the pressure in the cavity is slowly released to atmospheric pressure at a rate of 5-15 MPa / min. Step 5: Post-processing and product recovery The synthesized block is removed from the press, and the peripheral pressure transmission medium, heating element and sealing components are removed in sequence to peel off the boron-containing nano-polycrystalline diamond sintered body. The obtained sintered body is boiled in aqua regia or a mixture of concentrated sulfuric acid and concentrated nitric acid for 30 to 60 minutes to remove residual metal catalyst or impurity phases on the surface. Then it is ultrasonically cleaned with deionized water until the washing solution is neutral, and dried in an oven at 80 to 120 °C to constant weight to obtain the boron-containing nano-polycrystalline diamond finished product.

6. The method according to claim 5, characterized in that, The assembly comprises, from the inside out, a composite source blank, a heating element, a pressure transmitting medium layer, a conductive ring, and a sealing component. During assembly, it is ensured that the composite source blank, the heating element, and the conductive ring form a complete current loop.